Hubungan Antara Self Efficacy dengan Social Loafing Mahasiswa Fakultas Psikologi Universitas Putra Indonesia “YPTK” Padang - Ane Titisemita (Journal of Demography, Ethnography and Social Transformation, 2021)
The purpose of this study was to determine the relationship between self-efficacy and social loafing for students of the Faculty of Psychology, Universitas Putra Indonesia "YPTK" Padang. The study was conducted on 43 students, where the determination of the respondents was carried out using a sampling technique, namely incidental sampling. The data collection method uses a Likert model scale, namely the self-efficacy and social loafing scale. The data analysis method used for hypothesis testing is Product Moment (Pearson) correlation. Before testing the hypothesis, the assumption is tested using the normality test and linearity test. The results of data processing obtained p = 0.000 < 0.01 with a correlation coefficient of -0.741 which means the hypothesis is accepted. This shows that there is a very significant negative relationship between self-efficacy and social loafing in first and second year students of the Faculty of Psychology UPI "YPTK" Padang, with an effective contribution of 55%. So it can be concluded that the higher the self-efficacy, the lower the student's social loafing tendency. Conversely, the lower the self-efficacy, the higher the student's social loafing tendency. Keywords: Self efficacy, Social Loafing, Students